Uso del modelo tecnológico y diseño instruccional en cursos virtuales para el logro de aprendizajes significativos de informática en el nivel de bachillerato del Colegio Militar Tcrn. Lauro Guerrero de la ciudad de Loja, periodo octubre 2011 - febrero 2012. Lineamientos alternativos - Banda Álvarez, Gloria Karyna (2012)
The objective of the research was to determine the contribution of technology and instructional design model of virtual courses in achieving significant learning informatics in undergraduate level Tcrn Military College. Lauro Guerrero city of Loja, for which through the use of synthetic analytical methods, hermeneutical, descriptive, inductive and systemic as well as the application of interviews, surveys and observations made by the research population level cadets high school, teachers of the subject of computer and administrative staff of the institution, empirical information was obtained, it was processed, analyzed and subsequently confronted with theoretical references, allowing data from more representative decision with For each of the hypotheses, concluding that the technological infrastructure of COMIL-5 positively affects the achievement of significant learning about computers, because it meets the conditions and specifications that require this level of education, but to enhance their effectiveness is necessary to strengthen administrative technology infrastructure, implement specialized procedures in educational technology, formalizing the institutional and technological model train teachers in the selection and proper use of technological tools and virtual learning environments. As for the instructional design currently used in online courses, it is concluded that it is not conducive to the achievement of significant learning computer science undergraduate level, since there is not a plan that outlines proper design aimed at efficient use of the environment virtual learning as a teaching tool, which encourages the creation of a participatory environment, active and collaborative aimed at forging a positive attitude, critical, reflective around the themes developed and to allow effective evaluation from the constructivist approach to learning. Guidelines for the construction of alternative methodology used Deming cycle, that set a list of strategies to solve the problems presented by developing a continuous improvement plan tecnodocentes processes to achieve meaningful learning, based in teacher training in the development and implementation of a technological model and an instructional design that contribute to the effective inclusion of Information Technology and Communications in the process of learning the high school level of the Military School No. 5. Tcrn. Lauro Guerrero city of Loja.